Urgency of Insurance for Cultural Heritage Building in Surabaya - Hilda Yunita Sabrie (Universitas Airlangga, 2018)
The cultural heritage of a region is the identity and richness of history for the region. Given the importance of the existence of cultural heritage in an area, the local government should pay special attention to the continuity of its existence. Through inventory, listing the cultural heritages, maintenance until its restoration must be done properly and continuously. This is not only the responsibility of the local government, but it is the responsibility of all parties including the local community. But in practice, local government or society are less concerned about the existence of cultural heritage in the area. This research focuses on cultural heritage buildings in Surabaya because this city is one of the cities in Indonesia which has many buildings of cultural heritage with various conditions. Local governments need to act quickly and effectively to solve the problem, so the solution can be done by including third parties such as insurance companies engaged in the insurance of losses, which can help to cover some form of damage that occurred in the building of the reserve culture in Surabaya. From the problems mentioned above, the research method used is statute approach and conceptual approach.